Selective monitoring of the protein-free ADP-ribose released by ADP-ribosylation reversal enzymes. - Samuel Kasson (Public Library of Science (PLoS), 2021)
ADP-ribosylation is a key post-translational modification that regulates a wide variety of cellular stress responses. The ADP-ribosylation cycle is maintained by writers and erasers. For example, poly(ADP-ribosyl)ation cycles consist of two predominant enzymes, poly(ADP-ribose) polymerases (PARPs) and poly(ADP-ribose) glycohydrolase (PARG). However, historically, mechanisms of erasers of ADP-ribosylations have been understudied, primarily due to the lack of quantitative tools to selectively monitor specific activities of different ADP-ribosylation reversal enzymes. Here, we developed a new NUDT5-coupled AMP-Glo (NCAG) assay to specifically monitor the protein-free ADP-ribose released by ADP-ribosylation reversal enzymes. We found that NUDT5 selectively cleaves protein-free ADP-ribose, but not protein-bound poly- and mono-ADP-ribosylations, protein-free poly(ADP-ribose) chains, or NAD+. As a proof-of-concept, we successfully measured the kinetic parameters for the exo-glycohydrolase activity of PARG, which releases monomeric ADP-ribose, and monitored activities of site-specific mono-ADP-ribosyl-acceptor hydrolases, such as ARH3 and TARG1. This NCAG assay can be used as a general platform to study the mechanisms of diverse ADP-ribosylation reversal enzymes that release protein-free ADP-ribose as a product. Furthermore, this assay provides a useful tool to identify small-molecule probes targeting ADP-ribosylation metabolism and to quantify ADP-ribose concentrations in cells.